NARRACIÓN DE CUENTOS Y SU INCIDENCIA EN EL DESARROLLO DE LENGUAJE EN NIÑOS DE EDUCACIÓN INICIAL I, EN LA UNIDAD EDUCATIVA “QUINTILIANO SÁNCHEZ RENDÓN” CANTÓN BUENA FE. - VELIZ SALTOS JOHANNA MARIBEL (2024)
The present research focuses on analyzing the incidence of storytelling in the language development of children in Initial Education I in the "Quintiliano Sánchez Rendón" Educational Unit of the Buena Fe canton. Storytelling is recognized internationally as a fundamental pedagogical strategy to improve communication and cognitive skills in childhood, strengthening the ability to express and understand the world around children. The study has a mixed methodology approach, integrating descriptive and qualitative approaches, for this the classroom observation sheet is used to analyze the interaction and behaviors of the children, in addition to observing the methodological strategies of the teachers, an interview with 2 teachers was used. and a semi-structured survey for 30 parents in order to analyze the interactions and dynamics that are generated during storytelling activities in the classroom. As a result of the study, it was found that storytelling has a positive impact on children's language development, as well as a significant expansion of vocabulary and an improvement in students' oral expression. However, it is identified that insufficient pedagogical resources can be limiting in promoting the love of reading from an early age. It also analyzes how family interaction and support plays in the educational process, directly influencing the acquisition and strengthening of children's linguistic skills. This research highlights the importance of integrating motivational strategies and strengthening the bond between school and families to maximize the benefits of storytelling in the comprehensive development of Early Education I students. In conclusion, this study highlights the effectiveness of storytelling. Storytelling as a pedagogical tool to promote language development in early childhood, while identifying areas of opportunity related to resources and family participation, which must be addressed to further enhance the positive results of this educational practice.